1997
DOI: 10.1002/(sici)1096-9063(199709)51:1<56::aid-ps590>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of prosulfuron at pH 5: evidence for a resonance-stabilized triazine cleavage product

Abstract: : Prosulfuron is a herbicide for the selective control of broadleaf weeds in corn. In order to examine the e †ect of pH on the stability of prosulfuron in aqueous solution, a hydrolysis experiment was conducted in bu †er at pH 5, 7 and 9 utilizing [phenyl-14C] and [triazine-14C]prosulfuron. Prosulfuron was found to be stable under neutral and basic conditions and hydrolytically unstable under acidic conditions days). One of the major routes of deg-(T " D10 radation at pH 5 involved hydrolysis of the sulfonylur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 5 publications
(1 reference statement)
1
8
0
Order By: Relevance
“…Based on initial LC/MS analyses, three potential prosulfuron degradation products were identified that could have been present in the soil (Figure 7). These degradation products corresponded to ions of mass‐to‐charge (m/z) of 452, 425, and 254 (Figure 7) [ Bray et al , 1997; Kulowski et al , 1997]. Upon further investigation using LC/MS/MS, it was determined that the only degradation product present at detectable concentrations was the compound corresponding to m/z = 452.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on initial LC/MS analyses, three potential prosulfuron degradation products were identified that could have been present in the soil (Figure 7). These degradation products corresponded to ions of mass‐to‐charge (m/z) of 452, 425, and 254 (Figure 7) [ Bray et al , 1997; Kulowski et al , 1997]. Upon further investigation using LC/MS/MS, it was determined that the only degradation product present at detectable concentrations was the compound corresponding to m/z = 452.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure for prosulfuron and possible structures for the three potential degradation products observed by LC/MS [ Bray et al , 1997; Kulowski et al , 1997]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarmah and Sabadie suggested that the cleavage of the triazine ring was the most important degradation pathway for these herbicides under acidic conditions [33]. Similar degradation routes have also been proposed for prosulfuron hydrolysis in aqueous solution [38].…”
Section: Hydrolysis Pathwaysmentioning
confidence: 57%
“…Degradation of the triazines depends on ring cleavage of the compound, and for the triazine amines in sulfonylurea, chemical ring cleavage has been found only at or below pH 5 (Berger and Wolfe, 1996;Bray et al, 1997;Cambon and Bastide, 1997). This indicates, along with our mineralization data, that microbial degradation of the triazine part (as with the sulfonamide part) is the main mechanism of degradation of the hydrolysis products of metsulfuron-methyl.…”
Section: Effects Of Temperature and Plant Cover On Mineralization In mentioning
confidence: 99%